Occupational lifting during pregnancy and risk of fetal death in a large national cohort study - Mette Juhl; Katrine Strandberg-Larsen; Pernille Stemann Larsen; Per Kragh Andersen; Susanne Wulff Svendsen; Jens Peter Bonde; Anne-Marie Nybo Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: The aim of the present study was to examine the association between occupational lifting and the risk of fetal death according to gestational age. METHODS: We used data from the Danish National Birth Cohort (1996-2002). Among 71 500 occupationally active women, 2886 experienced a fetal death. Information on lifting and relevant covariates was collected in interviews around week 16 of pregnancy. The majority of fetal losses (N=2032) happened before the scheduled interview, and exposure data were collected retrospectively from these women. We analyzed early miscarriage (≤12 weeks), late miscarriage (13-21 weeks), and stillbirth (≥22 weeks), using Cox-regression models with gestational age as the underlying time variable. RESULTS: The adjusted early miscarriage risk increased with frequency of daily lifts and total burden lifted per day. For example, the hazard ratio was 1.38 [95% confidence interval (95% CI) 1.10-1.74] for a total weight load per day of 101-200 kg and 2.02 (95% CI 1.23-3.33) for a daily load >1000 kg as compared to non-lifters (P for trend <0.0001). Late miscarriage was associated with total daily weight load (P for trend=0.0073) but not with number of lifts per day. There was no association between occupational lifting and stillbirth. CONCLUSIONS: In the present study, the risk of miscarriage increased with the number of lifts and total burden lifted per day at work. There may be a case for advising pregnant women against heavy lifting in particular during early pregnancy.